2004
DOI: 10.1590/s0103-90162004000600007
|View full text |Cite
|
Sign up to set email alerts
|

Sensory acceptance of mixed nectar of papaya, passion fruit and acerola

Abstract: Nectars are beverages formulated with the juice or pulp of one or more fruits, plus water and sugar in concentrations resulting in a "ready-to-drink" product. Recently, the market for such products has greatly expanded. Fruit mixtures present a series of advantages, such as the combination of different aromas and flavors and the sum of their nutritional components. The objective of this work was to develop a nectar based on papaya pulp and passion fruit juice, enriched with the vitamin C present in acerola pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0
23

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 4 publications
5
19
0
23
Order By: Relevance
“…Sucos adoçados parecem ter a preferência do consumidor, conforme demonstrado por Matsuura et al (2004) no desenvolvimento de um néctar à base de polpa de mamão e suco de maracujá. A adição de açúcar à mistura de frutas diminuiu a acidez e influenciou positivamente a aceitação em até 17%.…”
Section: Teste De Aceitaçãounclassified
“…Sucos adoçados parecem ter a preferência do consumidor, conforme demonstrado por Matsuura et al (2004) no desenvolvimento de um néctar à base de polpa de mamão e suco de maracujá. A adição de açúcar à mistura de frutas diminuiu a acidez e influenciou positivamente a aceitação em até 17%.…”
Section: Teste De Aceitaçãounclassified
“…In the beverage segment, a new market that is opening up is that of juice originating from mixed fruit (Matsuura et al, 2004). The development of mixed fruit juice or nectar is a resource available to the industry to develop unique drinks such as, for example, those with new flavors, improved color and consistency, and moreover, mixed-fruit juices are an alternative for adding nutritional value (Sobhana et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Jothi et al (2014) reported that mixed squash prepared from 40 percent carrot juice incorporation with 40 percent papaya and 20 percent banana juice was highly acceptable and indicated the commercial scope for developing nutritious squash from carrot, papaya and banana juice. Matsuura et al (2004) showed that nectar produced with 37.5 percent papaya pulp, 7.5 percent passion fruit juice and 5.0 percent acerola pulp with addition of 15 percent sucrose was highly acceptable. Papaya pulp and sucrose positively affect the sensory acceptance of nectars.…”
Section: Papaya Beveragementioning
confidence: 99%